Mental Representation Level of Junior High School Students in Cell Biology Concept Based on Gender - Windyariani, S.; Sabilla, A. D.; Ramdhan, B.; Irawan, B. (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to determine the level of mental representation of seventh-grade junior high school students in cell concepts. The research method used was the explanatory sequential mix method with 60 research subjects. The instruments used in this research were the Mental Diagnostic Test (MDT), which consists of a reasoned true and false test, a symbolic test, and an imaging test. Based on the results obtained from the answers to the MDT instrument, it can be seen that the levels of mental representations are categorized into Initial mental representation, Intermediate mental representation 1, Intermediate mental representation 2, Consensus representation, and Target representation. The results show that on the MDT instrument, the average student is included in the intuition and experience mental model. The level of the mental representations of male students is higher than that of female students. The mental representation of the initial level, intermediate 1, and the target in male and female students have the same level; the difference occurs at the intermediate level 2 and consensus. Male students (30%) have higher intermediate level 2 than female students (20%). Furthermore, there are 10% male students and no female students at the consensus level. This research concludes that the information level profile of mental representation is identified as having the type of intuition and experience.